Impulsive buying dalam cashless society: Peran aksesibilitas fintech, literasi keuangan, dan self-control. - Ummi Setiyani; Suratno Suratno (Jurnal Pendidikan Ekonomi (JUPE), 2026)
This study aims to analyze the influence of fintech accessibility, financial literacy, and self-control on the impulsive purchasing behavior of economics students in Semarang. A quantitative approach was used through a questionnaire survey of 192 respondents selected using purposive sampling. Data were analyzed using multiple linear regression with the aid of IBM SPSS version 26. The results indicate that fintech accessibility has a significant effect on impulsive purchasing, suggesting that the ease and speed of digital transactions encourage unplanned purchasing decisions. Conversely, financial literacy does not have a significant effect, indicating a gap between financial knowledge and actual consumption behavior. Self-control has a negative effect on impulsive purchasing, but it is not statistically significant. This study contributes to the literature on financial behavior and provides practical implications for enhancing consumer awareness and self-control in the digital financial era.